Symptoms of anxiety and depression across adulthood and blood pressure in late middle age: the 1946 British birth cohort - Tikhonoff, Valérie (Lippincott Williams & Wilkins, 2014)
OBJECTIVE: Previous studies testing the hypothesis that symptoms of anxiety and depression increase blood pressure (BP) levels show inconsistent and limited findings. We examined the association between those symptoms across adult life and BP in late middle age. METHODS: Using data from 1683 participants from the MRC NSHD, we investigated associations between affective symptoms at ages 36, 43, 53 and 60–64 years and SBP and DBP at age 60–64. Multivariable linear regression was used to examine the effect on BP of affective symptoms at each age separately and as a categorical cumulative score based on the number of times an individual was classified as a ‘case’. Models were adjusted for sex, BMI, educational attainment, socio-economic position, heart rate, lifestyle factors and antihypertensive treatment. RESULTS: In fully adjusted models, we observed lower SBP in study members with case-level symptoms at one to two time-points [−1.83 mmHg; 95% confidence interval (CI) −3.74 to 0.01] and at three to four time-points (−3.93 mmHg; 95% CI −7.19 to −0.68) compared with those never meeting case criteria suggesting a cumulative inverse impact of affective symptoms on SBP across adulthood (P value for trend 0.022). Sex and BMI had a large impact on the estimates while not other confounders. Potential mediators such as heart rate and lifestyle behaviours had a little impact on the association. SBP at age 36 and behavioural changes across adulthood, as additional covariates, had a little impact on the association. A similar but weaker trend was observed for DBP. CONCLUSION: A cumulative effect of symptoms of anxiety and depression across adulthood results in lower SBP in late middle age that is not explained by lifestyle factors and antihypertensive treatment. Mechanisms by which mood may impact BP should be investigated.